UTILIZATION OF UNIVERSITY HEALTH CARE SERVICES AMONG UNDERGRADUATE STUDENTS IN GOMBE STATE UNIVERSITY-NIGERIA - HASSANA Y. BELLO; NASIRU ANAS; ABDULAZEEZ USMAN; FUNGO, W. ELKA (International Studies Journal)
The study examined the utilization of university health care services among undergraduate students in Gombe State University. The study employed accidental sampling technique to administer 601 copies of structured questionnaires to students that visited the university clinic for treatments. The findings of the study revealed that, the university clinic accommodate received more female students compared to male. The study found that most of the university staff are accommodative as showed by the majority respondents. The time given to students in the clinic always clashes with lectures. The study revealed the types of illnesses taken students to university clinic include indigestion/conspiration, cold fever, malaria fever, typhoid fever, headache and general body pain, feminal problems and antenatal services among pregnant women. The study shows that students indicated satisfaction with the treatment received. The study however revealed inadequate personnel, lack of drugs, unfriendly approach of staff, inadequate facilities and delay in administering health care services among the challenges students encounter in utilizing the university health care facilities. The study concluded by recommending the need for upgrading the university health care clinic with sophisticated medical equipment to enable diagnose of diseases mostly taken students to the university clinic. Also, more medical personnel should be employed to help the experienced and old medical staff mostly with increase in the population of students in the university. This research has further contributed to the literature on utilization of university health care services among undergraduate students. There was no any empirical research of this nature in the study area and on this note, the findings of the study differed from other previous related study in the university because it has showcased a new knowledge on perception, type of illnesses taken students to university clinic and level of satisfaction of the treatment received and challenges students encounter in accessing the university health care clinic.